Epidemiology of Intra-Cerebral Hemorrhage in Young Adult Patients - Melisa Melisa; Asra Al Fauzi; Anggraini Dwi Sensusiati (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2020)
Introduction: This study aimed to define the CT scan imaging of young adult intracerebral hemorrhage (ICH) patients in Dr. Soetomo General Hospital, Surabaya.Methods: This was an observational descriptive study. The data were collected retrospectively with medical records of 18 to 45 years old ICH patients who were treated in Dr. Soetomo General Hospital, Surabaya between 2014 and 2017. The collected data were then presented into tables.Results: 207 patients were identified in this study. The locations of the ICH were basal ganglia (45.89%), lobar (41.55%), thalamus (10.63%), brainstem (8.7%), cerebellum (4.83%), and others (3.86%). The volume of ICH varied from less than 30 cc (66.67%), 30 to 59 cc (27.54%), and more than 60 cc (5.8%).  Conclusion: The CT scan imaging of young adults ICH mainly had hematoma volume less than 30 cc and was mostly located in basal ganglia area then followed by lobar area.